Pertumbuhan Tujuh Klon dan Dua Varietas Tanaman Tebu (Saccharum officinarum L.) Ratoon Satu Di Desa Warujayeng, Kecamatan Tanjung Anom, Kabupaten Nganjuk - Dedi Suprayogi; Setyo Budi; Wiharyanti Nur Lailiyah (GEMA AGRO, 2023)
The facts show that the increase in sugar demand is not in line with the declining sugarcane production. The aim of the study was to determine the morphological characters, genetic diversity, growth and yield of sugarcane. The research was conducted at PG Lestari Sugarcane Research and Development Plantation (P3T) PT Perkebunan Nusantara X (PTPN X) Waru Jayeng Village,Tanjung Anom District, Nganjuk Regency in December 2022 – August 2023. Clone test materials SB01 UMG NX 22, SB03 UMG NX 22, SB04 UMG NX 22, SB11 UMG NX 22, SB12 UMG NX 22, SB19 UMG NX 22, and SB20 UMG NX 22, BL variety and PS881 variety. Observational variables consist of qualitative variables (stems, leaves and buds) and quantitative variables (stem height, stem diameter, number of stems, number of leaves, and brix). Data analysis used analytical descriptive, ANOVA, DMRT test, correlation test, genetic diversity, and heritability. Clone SB12 UMG NX 22 had the best growth on stem heights of 351.11 cm (38 MSK), 353.89 cm (40 MSK), 358.33 cm (42 MSK), 364.44 cm (44 MSK); number of sticks 9 sticks (38, 40, 42, and 44 MSK). Clone SB01 UMG NX 22 has the best brix values of 20.67% (40 MSK), 22.30% (42 MSK), and 24.24% (44 MSK). There is a correlation between growth and yield variables. There is genetic diversity that affects the growth and yield of sugarcane including high H2 (stem height, stem diameter, number of stems, number of leaves, and brix). Medium KKG (stem height, number of stems, and brix). Low KKG (stem diameter and number of leaves). High KKF (rod diameter). Low KKF (in stem height, number of stems, number of leaves, and brix).